Evaluation of the occurrence, degradation, and ecotoxicological significance of pharmaceuticals as emerging contaminants of concern in wastewaters and surface waters of the urban area in Costa Rica - Ledezma-Espinoza, Aura (Instituto Tecnológico de Costa Rica, 2023)
The widespread occurrence of pharmaceuticals in the environment has driven many countries to develop studies on pharmaceutical contamination and start monitoring programs to determine the baseline data of their water resources, strategies of water management and assessment of the environmental risks and potential exposure to human health and aquatic ecosystems. In this dissertation work, an insight of contamination levels with selected pharmaceuticals was first obtained from the analysis of impacted water systems that included the wastewaters of a hospital and a wastewater treatment plant, and the surface waters of the Virilla and Torres rivers from the Great Metropolitan Area in Costa Rica. Passive sampling with organic-diffusive gradients in thin-films (o-DGT) and quadrupole time-of-flight high resolution mass spectrometry was applied to detect and quantify time weighted-average concentrations of pharmaceutical contaminants in the water samples from the urban sampling sites. Measured concentrations ranged from 0.012 to 3610 ng L-1 among the studied pharmaceuticals (atenolol, sulindac, levofloxacin, carbamazepine, sulfamethoxazole, sulfapyridine and sulfamethazine). All target molecules were ubiquitously detected in the surface waters and the wastewaters of the studied sites. In addition, a risk assessment was done of target pharmaceuticals for single parent compounds and mixtures in aquatic media. It was found that at concentration levels and exposure times analyzed in this study, sulfamethoxazole, levofloxacin and sulindac posed a potential risk to aquatic organisms. Overall, the results demonstrated the occurrence of varied class of pharmaceuticals during the long period of sampling, however additional monitoring studies are recommended to well-assess the actual effects of these compounds in the sampled urban waters. To our knowledge, this is the first study to assess the occurrence and risk assessment of sulindac on aquatic ecosystems using o-DGT passive sampling. Second, in this research, a fundamental study on elucidation of kinetic behaviour and photodegradation pathways in water for sulindac direct photolysis was developed. A novel kinetic mechanism was proposed in which sulindac exhibits a consecutive reaction pathway, with pseudo-first order kinetics for rapid and reversible Z to E isomerization, to undergo after photoequilibrium, a second-order degradation of the isomers in the presence of the new photodegradation products. Two novel and major byproducts were identified, and the results demonstrated a greater persistence of sulindac at relevant environmental conditions of UV A and pH 7, with a degradation pathway mainly photoinduced, enhanced by acidic conditions. Furthermore, this chapter demonstrated an approach to carry out kinetic studies under challenging conditions. The previous findings helped to better understand the fate and presence of selected pharmaceuticals in the aquatic matrices to define suitable treatment systems. A novel irradiated cellulose PEDOT composite was prepared as photocatalyst to remove pharmaceutical contaminants under ambient conditions. The I-Cell-PEDOT composite enhanced the photodegradation of sulindac and carbamazepine from neutral aqueous system under UV-A radiation, reaching photocatalytic removals of 89% for sulindac and 30% for carbamazepine within 7 h of treatment. The new treatment showed its potential to be used as an option for advanced removal processes of pharmaceutical pollutants from water sources. Monitoring programs in natural and treater waters as well as fundamental studies on fate of pharmaceuticals and removal treatment technologies are needed to better understand the pollution situation in the aquatic environment, thus this research was aimed to generate knowledge about pharmaceutical contamination and its evaluation in waters impacted by urban activity in the Great Metropolitan Area of Costa Rica, to contribute to the decision making and sustainable water management for better protecting of the environment and public health.
Tesis (Doctorado en Ciencias Naturales para el Desarrollo con énfasis en Gestión y Cultura Ambiental) Instituto Tecnológico de Costa Rica. Universidad Estatal a Distancia. Universidad Nacional, Doctorado en Ciencias Naturales para el Desarrollo, 2023.
Keywords: Contaminantes orgánicos emergente; Productos farmacéuticos; Muestreo de agua; Evaluación de riesgos; Fotólisis; Fotocatálisis; Irradiación gamma